2015
DOI: 10.1002/jclp.22185
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness in the Treatment of Borderline Personality Disorder: A Quasi‐Experimental Study

Abstract: Effect sizes were similar to meta-analytic findings on (a) forgiveness interventions and (b) reductions in psychiatric symptoms in DBT. Participant feedback suggested elements for further development. A randomized controlled trial is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…It showed benefits only for empathy (Nation et al, 2018). Thus it is important to determine whether REACH Forgiveness methods are capable of generating not only benefits to forgiveness and unforgiveness, but also other closely related outcomes (e.g., involving emotional expressivity and mood and also self-esteem) that have been shown to be positively affected in United States samples (Sandage and Worthington, 2010;Sandage et al, 2015;Worthington et al, 2015;Wade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It showed benefits only for empathy (Nation et al, 2018). Thus it is important to determine whether REACH Forgiveness methods are capable of generating not only benefits to forgiveness and unforgiveness, but also other closely related outcomes (e.g., involving emotional expressivity and mood and also self-esteem) that have been shown to be positively affected in United States samples (Sandage and Worthington, 2010;Sandage et al, 2015;Worthington et al, 2015;Wade et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the authors also assessed and supplied data based on trait measures of attachment anxiety and avoidance, so it is categorized as such in the analysis. The second experimental study aimed to test a psychoeducational intervention to promote forgiveness in a clinical sample; only the baseline global forgiveness and trait attachment data were included in the meta-analysis (Sandage et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Two papers were identified that used revenge as a measure of (lack of) forgiveness and one paper that used grudge holding (Edwards, 2012; Reis, 2018; Sandage et al, 2015). This represents inadequate power to assess the effect of attachment on these outcomes, and so they were not included in the current analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, Sandage et al . 24 developed a module based on forgiveness to be added to outpatient DBT. In one study, participants who completed this module showed improvements in forgiveness and decreases in psychiatric symptoms and attachment insecurity during the module and up to 6 weeks after.…”
Section: Adjunctive and Web-based Interventionsmentioning
confidence: 99%